Pertumbuhan Bibit Kelapa Sawit pada Tanah Gambut Berbagai Ketinggian Genangan - Holidi Aminudin; Etty Safriyani; Warjiyanto Warjiyanto; Sutejo Sutejo (Faculty of Agriculture, Universitas Gadjah Mada jointly with PISPI, 2015)
The area of dry land for plantation cultivation is limited, so peatland would be an alternative development. Adaptation of plant oil palm on the long inundation need to be investigated. This study aims to determine the growth response of oil palm seedlings in peat with some duration of flooding. The research was conducted in the experimental farm of the Faculty of Agriculture, University of Musi Rawas at an altitude of 110 m above sea level on March to June 2014. This study used a randomized block design (RBD) consists of six treatments and four replications. Treatment includes without flooding, duration of flooding 10, 20, 30, 40 and 50 days. The results showed that oil palm seedlings can survive up to 50 days of flooding. Long flooding inhibits the growth of plant height, number of leaves, reducing the amount of leaf chlorophyll. flooding also causes morphological changes in the root of the formation of adventitious shoots.